Effects of principal stress rotation and intermediate principal stress changes on the drained monotonic and undrained cyclic behavior of clean and nonplastic silty Ottawa sands formed underwater - Tastan, Erdem Onur, author; Carraro, Antonio, advisor (Colorado State University. Libraries, 2009)
A state-of-the-art dynamic hollow cylinder apparatus was used to systematically study the effect of drained changes in the major principal stress direction (a, taken from the vertical) and intermediate principal stress coefficient (b) on the (1) drained static and (2) undrained cyclic stress-strain responses, and (3) liquefaction resistance of clean and nonplastic (NP) silty Ottawa sands formed underwater. A modified slurry deposition method was developed to reconstitute HC clean and NP silty Ottawa sand specimens in a way that resembles the actual field deposition of these soils underwater. Using a new density gradient mold developed during this study, the maximum local deviations of relative density (D R) and fines content (FC) from their global averages were determined to be as small as (or lower) than the deviations obtained for similar reconstitution methods typically used for solid triaxial specimens. Drained increases in a and/or b at constant mean normal effective stress and octahedral deviator stress were shown to induce strains as large as those induced during anisotropic- K0 consolidation, with the NP silty Ottawa sand typically yielding larger strains than the clean Ottawa sand at similar states. As a increased, the sands exhibited weaker undrained cyclic responses. However, the relative effect of a on soil response appears to be less significant for Ottawa sands with NP silt content between 11% and 15%. Increase in b improved the liquefaction resistance of the sands. However, when both a and b were greater than zero, their combined effect typically decreased the liquefaction resistance of the sand, suggesting that a may play a more dominant role on the undrained response of the sand than b. Undrained instability was observed in many tests carried out on anisotropically consolidated specimens subjected or not to a and/or b changes. Occurrence of undrained instability depends upon the cyclic stress ratio, a, b, DR and FC of the soil. The results of this study indicate that liquefaction analyses based on axisymmetric parameters may be unconservative for most types of geotechnical applications since axisymmetric conditions do not account for the effect of a on the liquefaction resistance of the soil. Appropriate evaluation of the liquefaction potential of a soil requires consideration of both a and b, although the major controlling mechanism might be associated with the mechanical response imparted by drained principal stress rotation. The results obtained in this study may be used to develop new or improve and calibrate current constitutive models that address soil anisotropy and more realistic loading conditions in geotechnical analyses. Typical applications of such advanced models include geotechnical analyses of slope stability, design of foundations, dams, embankments, pavement subgrades, and retaining structures, particularly those involving tailings, hydraulic fills, and alluvial or marine deposits of sands with fines formed underwater.
Keywords: drained; Ottawa sands; silty; stress; underwater; hydrologic sciences; civil engineering